PENINGKATAN AKTIVITAS FISIK DAN PEMANFAATAN PEKARANGAN RUMAH UNTUK TANAMAN OBAT KELUARGA (TOGA) SEBAGAI GERAKAN MASYARAKAT HIDUP SEHAT (GERMAS) DI KELURAHAN KENALI ASAM BAWAH - Faridah Faridah; Iin Indrawati (Sekolah Tinggi Ilmu Kesehatan Baiturrahim Jambi, 2019)
Health is an investment to develop the economy and has an important role in poverty alleviation efforts. Health problems that exist in the community are very many and varied. House-to-house tracking is the most effective way to find out how real health problems are being faced by the community. The target will be achieved by doing physical activities such as sports and cleaning the house, eating vegetables and fruit so that the body is healthy, regular health checks, even in good health, not smoking and not consuming alcohol, cleaning the living environment, using the toilet. While the expected output is doing homework such as washing dishes, washing clothes, mopping and so on is physical activity, it is better if coupled with exercise, such as morning walks, increasing consumption of fruits and vegetables, stopping smoking and not consuming alcoholic beverages, medical checks up although in a healthy condition, together with the surrounding community do the work of cleaning the local environment, using the latrine properly as a place of disposal.The method of implementation carried out is by following counseling about how to run a healthy lifestyle in the family and surrounding environment, counseling about how families and communities run a healthy lifestyle so as to avoid various diseases.